2020
DOI: 10.1111/hiv.13016
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare delivery for HIV‐positive people with tuberculosis in Europe

Abstract: Background In a 2013 survey, we reported distinct discrepancies in delivery of tuberculosis (TB) and HIV services in eastern Europe (EE) vs. western Europe (WE). Objectives To verify the differences in TB and HIV services in EE vs. WE. Methods Twenty‐three sites completed a survey in 2018 (EE, 14; WE, nine; 88% response rate). Results were compared across as well as within the two regions. When possible, results were compared with the 2013 survey. Results Delivery of healthcare was significantly less integrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 16 publications
1
16
1
Order By: Relevance
“…It is very likely that better integration of clinical services and diagnostic capacity can decrease delays in diagnosing TB in PLWH. HIV and TB services in Eastern Europe are only provided in one place at about 36% of health care centers [ 32 ]. While evidence of the effect of integrated health care on delayed diagnosis is not available, studies in Sub-Saharan Africa have shown improved HIV and TB treatment outcomes when integrating HIV and TB care [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is very likely that better integration of clinical services and diagnostic capacity can decrease delays in diagnosing TB in PLWH. HIV and TB services in Eastern Europe are only provided in one place at about 36% of health care centers [ 32 ]. While evidence of the effect of integrated health care on delayed diagnosis is not available, studies in Sub-Saharan Africa have shown improved HIV and TB treatment outcomes when integrating HIV and TB care [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Rwanda, expanded access to systematic Xpert testing and standardized treatment of Rifampicin-resistant TB in both HIV-seronegative and PLWH led to the reduction of diagnostic and treatment delays resulting in reduced mortality [ 35 ]. In Eastern Europe, Xpert was used as part of routine work-up at almost all (92%) clinics in 2018, which is a major improvement compared to 2013 (54%) when the present study was conducted, so we cannot rule out improvements to delayed diagnosis in the meantime [ 32 ]. A promising additional tool for rapid diagnosis and treatment initiation at the point of care for PLWH regardless of site of TB infection is the urine-based lipoarabinomannan (LAM) test [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients were even less likely to be treated for TB and HIV by the same physician and no improvement in the availability of OST was found [39,72]. A slightly positive trend is found for HIV treatment strategies, where earlier initiation of ART regardless of CD4 count is the standard of care in 62% compared with 46% of clinics in 2013 [39,72]. Officially, all countries in Europe now have the treat-all policy [44].…”
Section: Problem 5: Fragmented Healthcare Systemsmentioning
confidence: 99%
“…Another important observation is that despite of DST patterns becoming available during treatment, patients were not switched to a more effec-tive regimen. This could reflect reduced drug availability at the time of study and may have subsequently improved [16,17]. Bedaquiline, for example, was not available at the time of the study, but it is now.…”
Section: Tuberculosis Research and Treatmentmentioning
confidence: 99%